The Dynamic of Betawi in Colors - Mita Purbasari; M. Dwi Marianto; M. Agus Burhan (Mudra Jurnal Seni Budaya, 2016)
Color is no longer a small issue; it is one of the very important for artistic Workers. In daily life, using color is very common and rarely to be observed or pursued deeply, because color as a one ofthe design element was more digested and processed by feeling, not of thought, so often considered something unimportant. Color is a lot and often used for aesthetic and communication. Without realizing it, color gives special identity to certain things in time, place, and situation ofits own. Although widely used in daily life practically, color has symbolic and decorative characteristic in Indonesia, especially in Jakarta. These colors become characteristic in every performance ofculture and art in Jakarta (Betawi). Betawi have a unique typical codification color that reï¬‚ects the characteristic ofBetawiâ€˜s life, however by the presence ofmassive urbanization in Jakarta, then changed Betawi culture including codification of colors. This research ï¬nd out how Betawi gives the typical color naming and its relationship with the social cultural circumstance of the moment. And the result also expected to introduction of Betawi color in particular, and also to build a Betawi atmosphere for purposing related to interior, products, and environment.Key words: color naming, Betawi, culture